Why are the elite in China motivated to promote growth? - Xiaowei Zang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Rapid economic development in China in the post-1978 era has been considered 'intriguing' and 'puzzling' since it occurred under the dominance of the Chinese Communist Party - the fusion of politics and economics is supposed to be a powerful impediment to market growth. Scholars have proposed different accounts to explain this paradox, with particular emphasis on the role of the political elite in economic progress. This paper contributes to this literature by studying why the political elite are motivated to promote economic development in China. It argues that like politicians in other types of political regimes, autocratic leaders are interested in high growth rates. It also studies the historical development of China's developmental elites to understand their motivations for economic growth in the reform era. To better understand whether or not elites in developing countries promote economic growth, scholars should focus on factors such as historical experience, political stability, leadership turnover, or elite perceptions about the impact of growth on their hold on power rather than the differences between autocracy and democracy.
Keywords: O53; P20; P26; P27; 330; China; democracy; autocracy; development; growth; elites